Professional qualification, mental health and public social policies: nowadays challenges - Jennifer Carvalho Araújo, Laína; Goulart Joazeiro, Edna Maria (Argumentum, 2020)
The article analyses professional training, its relationship with the field of Mental Health and its links with essential public social policies in Brazil, a country strongly marked by social inequality. It is qualitative research, at master’s level, which undertakes an analytical-conceptual discussion around the legal framework of Brazilian Mental Health Policy and correlates it to the historical dialogue in the field of Social Work. For this, secondary sources of information are used to analyse the historical GPAs of students on the UFPI Social Work Course between 1987 and 2018, inquiring into the relationship between training in the fields of knowledge and interventions. The challenges of mental healthcare are analysed in a time of crisis of capitalism, with a predominance of neoliberal policies, which tensions and confronts the achievements of the Sanitary and Psychiatric Reforms and the defence of the right to life.